Key Economic Growth Factors in Poland and Selected Countries of the World During the Years 2005-2013 - Spychała, Marcin (Studia Oeconomica Posnaniensia, 2015)
The main purpose of this article is to present the dynamics of GDP and to indicate the factors influencing economic growth during the recent financial crisis in the Polish economy and in selected countries between 2005 and 2013. In comparison to other European Union member states and other countries of the OECD, Poland recorded the highest level of economic growth in 2009. The negative effects of the financial crisis included a reduction in private consumption and in the investment demand of companies, with investment demand decreasing more significantly than private consumption. The financial crisis also resulted in decreased levels of exports and imports in OECD and EU countries.